(untitled) (Journal of Hama University, 2024)
The research deals with the study of the effect of synchronizing estrus by using the prostaglandin in dairy cows in order to decrease the rest period and the calving interval period. The observation of estrus in cows and inseminating them at the optimum time is one of the necessary steps to manage reproduction in the dairy herd. The cows were taken from one of the special breeding farms in the countryside of Al Qusayr, in Zyta district, which had given birth more than 80 days ago, without the appearance of estrus. The cows were examined by rectal palpation to ensure the presence of the corpus luteum. 30 cows were taken and those cows were divided into two groups, the first group (nx=23) group; the experiment and the second group (nc=7), the control group. The first group was injected with prostaglandin a dose of 500 µg intramuscularly and these cows were monitored for 3-4 days to determine the time of estrus occurrence. GnRH dose 50 µg intramuscularly immediately after insemination ˛ As for the 6 cows that did not show estrus after the first injection, the 6 cows were injected with prostaglandin again after 14 days from the date of the first injection and when estrus appeared, they were artificially inseminated with a dose of GnRH hormone. The control group injected 2 ml of physiological solution intramuscularly. The results of the study showed that there were significant differences at the value (P<0.05) between the study groups, as estrus appeared by 100% in the experimental group, while estrus did not appear in any animal in the second group. The average time of onset of estrus in the experimental group was (31.13 ± 3.63) hours and the pregnancy rate was 100% for all cows of the group in the experiment group, while no cows became pregnant in the control group. We conclude that hormone therapy with PGF2α supported the work of ovaries after calving by dissolving the CL and helped to decrease the rest period. This could be a guiding principle for a targeted breeding system in managing herds of dairy cows to have one newborn per year from each cow.